Effect of drought for growth parameters and pigment complex of wheat lines obtained from interspecific crosses (Experimental biology, 2018)
Deficit of water is a key stressor in global climate change conditions. The studying the influence of nucleus-cytoplasm relations can be helped to the better understanding of the process of plant adaptation to drought conditions. The aim of the study was the analyze of changes in growth parameters and pigment complex of seedlings of hybrids and alloplasmatic lines of wheat, obtained as a result of interspecific crosses, when exposed to induced drought. Investigated the 10-day wheat seedlings, which was growed in optimal and stressful conditions simulated in water culture. The content of chlorophyll and carotenoids of leaf plates was determined spectrophotometrically in alcohol extracts. It is shown that the change in the growth activity of seedlings is determined not only by the activity of the root system under drought conditions, but may be associated with optimization in the photosynthetic apparatus. It is noted that a combination of nuclei and cytoplasm belonging to different species can both improve and worsen important physiological parameters of stress resistance and photosynthetic activity. The most tolerant to drought alloplasmic lines D-d-05 b, D-b-05, D-41-05 and the most sensitive forms – allolinia D-f-05 and hybrid A1 were identified.Key words: wheat, interspecific hybrids, alloplasmic lines, drought tolerance, photosynthesis